Coventry's medieval suburbs : excavations at Hill Street, Upper Well Street and Far Gosford Street 2003-2007 - Mason, Paul (Archaeopress archaeology., 2017)
Reports the results of 2003-2007 excavations at Hill Street, Upper Well Street and Far Gosford Street, three suburban streets which stood directly outside the city gates of Coventry for much of the medieval period.